KNOWLEDGE, ATTITUDE OF TAPEWORM AND RAW MEAT EATING BEHAVIOR IN NANGLAE SUB-DISTRICT, MUANG DISTRICT, CHIANG RAI PROVINCE - Nunloi, Sunattra; Muangmool, Jutamas; Ruankham, Watcharapong (Life Sciences and Environment Journal, 2017)
The objective of this research is to study the knowledge, attitude towards tapeworm infection and raw meat eating behavior in Nanglae Sub-District, Muang District, Chiang Rai Province. The 414 samples is selected by multi-stage sampling, collected data by using the questionnaire and analysis by percentage, average and standard deviation. The results are 66.92% of good knowledge level, 93.71% of good attitudes level and 71.26% is raw meat eating behavior. At that time, a few another people are not emphasis about the tapeworm infection. Therefore, the staff of public health should to lead all educate them to change eating behavior.